PENGARUH FAKTOR LINGKUNGAN RUMAH TERHADAP TUBERKULOSIS PARU: SEBUAH KAJIAN SISTEMATIS DI INDONESIA: Literature Review - Rizkyansyah, Alif; Setiani, Onny; Astorina YD, Nikie (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
Indonesia was the 3rd country with the highest number of tuberkulosis sufferers in the world. The high number of tuberkulosis (TB) in Indonesia was related to various factors in the home environment. Population density, poor housing conditions, limited access to health services, low nutritional status, social and economic factors, high population mobility, and inappropriate treatment patterns were some of the main causes. A study was conducted to investigate the relationship between the home environment and the occurrence of pulmonary tuberkulosis in Indonesia. A systematic review was employed in this study, utilizing a sample of 15 pertinent journal articles. The data collection approach encompassed the exploration of articles aligned with the research objectives in designated databases, namely Google Scholar, Portal Garuda, Science Direct, ProQuest, and Springer Link, following defined inclusion and exclusion criteria. The Gathered data were organized into tables, and a table for data extraction was formulated. The identification of home environmental risk factors and data analysis were conducted using meta-synthesis (qualitative). The results of the research indicated that out of the 15 articles obtained in the final databases, factors such as ventilation, humidity, temperature, lighting, income , diabetes mellitus, and a history of household contacs were established as correlated with prevalence of pulmonary tuberkulosis in Indonesia. Home environmental factors, including ventilation, humidity, temperature, lighting, income, diabetes mellitus, and history of household contacts, influenced pulmonary tuberkulosis in Indonesia